Comics and Fanzines as educational-artistic constructs (Revista NUPEART, 2023)
Invited to write to Revista Profartes, to assist an understanding "for a project of living knowledge, consistent and consequent with Brazilian contemporaneity", as it was explained to me, I decided to accept knowing that I could talk about my experience as an artist and how I have been reflecting on the education when using the art of my area, specifically, poetic comics and artistic fanzines, believing that my interest would allow a text related to the magazine's proposal. Thus, I decided to write through a personal narrative that, I believe, encompasses a brief review of my past as a school student and allows an understanding of where I arrived and the reasons that guide my didactics and artistic expressiveness, also demonstrated in this text. The main bibliographic reference is from G. Andraus, E. dos Santos Neto and H. Magalhães.
Keywords: Creative Practice as Research; Ephemeral art; Theater at school